The Relationship Between Authoritarian, Democratic, And Permissive Parenting Styles And Coping Strategies In Dealing With Work Stress In A Jakarta Financial Company - Hendriana Hendriana (International Journal of Health Engineering and Technology, 2026)
In a competitive work context with tight business competition in financial companies, this can affect employee stress levels at work. The importance of understanding how to develop coping strategies when facing stress is crucial for developing mental health programs in the workplace. This study aims to determine the relationship between authoritarian, democratic, and permissive parenting styles received during childhood and the coping strategies used to manage work stress among employees in financial companies in Jakarta. This research method used a quantitative cross-sectional design. The study population included employees working in financial companies in Jakarta. The study sample consisted of 89 respondents selected through purposive sampling with the criteria of having worked for more than 3 months and having a productive age range between 20 and 58 years. The research instruments used included a parenting style scale questionnaire to measure parenting styles (authoritarian, democratic, and permissive) and a Ways of Coping Questionnaire to measure coping strategies used when stress occurs. The results of the study indicate that there is a relationship between authoritarian parenting patterns and coping strategies in dealing with work stress with a p-value of 0.0001 smaller than the alpha value (α = 0.05), for democratic parenting patterns there is also a relationship with coping strategies (p-value 0.0001 > 0.05) and likewise with permissive parenting patterns there is a relationship with coping strategies (p-value 0.0001 > 0.05). The conclusion of this study shows that authoritarian, democratic and permissive parenting patterns in childhood have a long-term impact on the way individuals determine coping strategies when dealing with work stress. Of course, the practical implications of this study still need to maintain a balance of coping strategies in dealing with work stress, in order to maintain mental health.